2021
DOI: 10.1123/japa.2020-0151
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor Walking Test With a Global Positioning System Device as an Additional Tool for Functional Assessment of Older Women

Abstract: The primary aim was to assess the test–retest reliability of an outdoor walking test with a global positioning system device in older women in a community setting. In addition, correlations between the suggested test and various tests recommended to evaluate muscle strength, walking speed, and self-perceived health status in older adults were studied. The study included 40 women aged 68 (SD = 5) years. The primary outcomes were total walked distance and mean walking speed. The secondary outcomes were lower-bod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…with claudication. Their accuracy [12,13], reliability [14] and validity [12,13,15] have been confirmed. It has also been shown that the results of the outdoor walking test correlate with the tools used so far to assess walking abilities [11,12].…”
Section: Introduction and Objectivementioning
confidence: 69%
See 1 more Smart Citation
“…with claudication. Their accuracy [12,13], reliability [14] and validity [12,13,15] have been confirmed. It has also been shown that the results of the outdoor walking test correlate with the tools used so far to assess walking abilities [11,12].…”
Section: Introduction and Objectivementioning
confidence: 69%
“…The results were analysed by a trained operator. Test-retest reliability of the outdoor marching test using the Garmin Forerunner® 310XT has been validated in the authors' previous research [15]. The weather conditions during each test, such as wind speed, precipitation and temperature, were recorded from a local weather station.…”
Section: Methodsmentioning
confidence: 99%